2002
DOI: 10.1097/01.asn.0000016445.29513.ab
|View full text |Cite
|
Sign up to set email alerts
|

Serum Glomerular Permeability Activity in Patients with Podocin Mutations (NPHS2) and Steroid-ResistantNephrotic Syndrome

Abstract: Abstract.A plasma factor displaying permeability activity in vitro and possibly determining proteinuria has been hypothesized in idiopathic focal segmental glomerulosclerosis (FSGS). In vitro permeability activity (P alb ) was determined in sera of five patients with autosomal recessive steroid-resistant nephrotic syndrome (NPHS2), an inherited condition indistinguishable from idiopathic FSGS on clinical grounds, but in which proteinuria is determined by homozygous mutations of podocin, a key component of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 18 publications
(14 reference statements)
3
54
1
2
Order By: Relevance
“…22,23 Carraro et al analyzed five patients with autosomal recessive steroid-resistant nephrotic syndrome (SRNS) (NPHS2) for serum glomerular permeability activity (Palb), and found high pretransplant Palb in all cases, equivalent to values observed in idiopathic FSGS. 24 In the PodoNet cohort, circulating suPAR levels were higher in familial FSGS and FSGS with documented NPHS2 mutations, and the difference remained significant after adjustment for other covariates. Our results justify larger cohort studies, with more comprehensive assessment of FSGS-associated mutations including TRPC6.…”
Section: Discussionmentioning
confidence: 86%
“…22,23 Carraro et al analyzed five patients with autosomal recessive steroid-resistant nephrotic syndrome (SRNS) (NPHS2) for serum glomerular permeability activity (Palb), and found high pretransplant Palb in all cases, equivalent to values observed in idiopathic FSGS. 24 In the PodoNet cohort, circulating suPAR levels were higher in familial FSGS and FSGS with documented NPHS2 mutations, and the difference remained significant after adjustment for other covariates. Our results justify larger cohort studies, with more comprehensive assessment of FSGS-associated mutations including TRPC6.…”
Section: Discussionmentioning
confidence: 86%
“…A recent report described assays of glomerular permeability in five patients with recessive NPHS2-associated NS (46). Plasma permeability activity was high in all cases.…”
Section: Familial Ns: Recessivementioning
confidence: 95%
“…These inhibitory serum factors may be normal serum components such as apolipoproteins E and J (20). Further studies found that urine of patients with FSGS neutralize the PF activity of the serum, suggesting loss of an inhibitor in the urine (21), that may play a central role in the process after kidney transplantation and possibly also in the original disease (17). These findings suggest the deficiency of an inhibitor to the normally occurring PF as a primary cause for proteinuria.…”
Section: Fsgs In Native Kidneysmentioning
confidence: 89%
“…Rarely PF may be present in patients with podocin (NPHS2) mutations. High pretransplant P alb was found in 5 children with autosomal recessive podocin mutations, in which FSGS recurred after transplantation in four out of five (17). Since the PF is mildly anionic, it is unlikely that the effect of this factor is to neutralize the anionic sites on the GBM.…”
Section: Fsgs In Native Kidneysmentioning
confidence: 99%
See 1 more Smart Citation